Association between prediabetes and the risk of atrial fibrillation: a systematic review and meta-analysis - Li, Yongchao; Deng, Ju; Li, Li (Frontiers in Endocrinology, 2026)
BackgroundAtrial fibrillation (AF) is the most common sustained cardiac arrhythmia and a major contributor to morbidity and mortality. Although diabetes is a well-established risk factor for AF, the role of prediabetes—a modifiable metabolic condition—remains uncertain. Clarifying this relationship may help identify individuals at risk and guide early preventive strategies.MethodsWe performed a systematic review and meta-analysis of cohort studies identified through PubMed, Embase, and Web of Science databases up to November 21, 2025. Studies reporting adjusted hazard ratios for incident AF in adults with prediabetes compared with normoglycemic controls were included. Pooled estimates were calculated using random-effects models, and heterogeneity was assessed using the I² statistic. Prespecified subgroup analyses explored variations by definition of prediabetes, geographic region, follow-up duration, age, and sex. Publication bias was evaluated using Egger’s and Begg’s tests.ResultsTwelve independent datasets from 11 cohort studies, including over 15 million participants and 277,164 incident AF cases, were analyzed. Prediabetes was associated with a modest but statistically significant increased risk of AF (pooled hazard ratio: 1.20; 95% confidence interval: 1.08–1.35), with substantial heterogeneity. Sensitivity analyses showed consistent results. Subgroup analyses indicated a numerically stronger association in Asian populations than in Europe and North America; this finding should be interpreted cautiously given heterogeneity and limited studies per subgroup. Other subgroup analyses were broadly consistent, and overall evidence of publication bias was limited.ConclusionPrediabetes is associated with increased AF risk across diverse populations. Given the observational design, these findings indicate association rather than causation. Early identification and management of prediabetes may provide an opportunity for AF prevention.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD420251233423.